2017
DOI: 10.18280/ijht.350107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment temperature on the structure and tribological properties of nanometer lanthanum borate

Abstract: Nanometer lanthanum borate was prepared by ultrasonic-assisted chemical precipitation. X-ray diffraction and a laser particle size analyzer were used to study the heat treatment temperature on the micro-structure of the nanoparticles, and the tribological properties of nanoparticles were explored for friction and wear using a MMU-10G testing machine. The results show that the heat treatment temperature not only determines the crystallization degree and crystal type of nanometer lanthanum borate, but also great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Moreover, there were two broad humps centered at 28.5°and 45.6°with diffuse peaks, indicating that LBN-1 and LBN-2 are amorphous. 26,38 The sharp peak in the XRD pattern of LBN-2 at 31.4°was steeper than LBN-1, which possibly attributed to the longer treatment duration of the hydrothermal process. Figure 5(b) shows the variation of absorbance at 382 nm over time.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, there were two broad humps centered at 28.5°and 45.6°with diffuse peaks, indicating that LBN-1 and LBN-2 are amorphous. 26,38 The sharp peak in the XRD pattern of LBN-2 at 31.4°was steeper than LBN-1, which possibly attributed to the longer treatment duration of the hydrothermal process. Figure 5(b) shows the variation of absorbance at 382 nm over time.…”
Section: Resultsmentioning
confidence: 95%
“…[17][18][19][20] As confirmed by many papers, [21][22][23][24][25] lanthanum borate nanoparticles are one of the highly efficient green lubricant additives owing to their active elements such as La and B, which possess excellent anti-wear properties under high load. Wang and Huang 26 found that the tribological performance of 150 N base oil was improved by lanthanum borate nanoparticles, but the larger size lanthanum borate nanoparticles resulted in exacerbate abrasive wear and reducing tribological performances. Unfortunately, the mechanisms of protective film formation lubricated with different sizes of lanthanum borate nanoparticles have not been further discussed in these research studies.…”
Section: Introductionmentioning
confidence: 99%
“…After the temperature increased to 400~800 ℃, the sample basically lost its strength. Fortunately, under the high temperature of 200 ~ 400 ℃, the compressive strength of XS-reinforced AASCM sample plunged under the high temperature of 200~400 ℃ [32]. The XS managed to enhance the compressive and flexural strengths of the sample.…”
Section: Mechanical Properties Of Aascm Reinforced By Different Fibermentioning
confidence: 99%
“…Ageing is mainly due to polymer chain degradation, characterized by the oxidation of the macromolecules accompanied by morphological changes [13][14][15]. As such, FTIR spectroscopy can be regarded as a powerful technique to identify the different oxidation products developing during ageing and allowing also to quantify their concentration changes upon time.…”
Section: Introductionmentioning
confidence: 99%